(untitled) - Myers, Norman (London, 1990)
The book is about: Global warming and lightning political change, super technology and famine, chaos theory and biotechnology, mass extinctions and a chance of world-peace--what kind of a future can we expect? Using Gaia's world-renowned graphic style, this far-sighted and challenging book provides a toolkit for future choice, and offers hope--but hope dependent on a radical shift in human lifestyle, perception, and spirit.
Keywords: Chính trị thế giới,World politics; 1985-1995,1985-1995